2019
DOI: 10.1126/sciadv.aax2166
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive variants of CSDE1 associate with autism and interfere with neuronal development and synaptic transmission

Abstract: RNA binding proteins are key players in posttranscriptional regulation and have been implicated in neurodevelopmental and neuropsychiatric disorders. Here, we report a significant burden of heterozygous, likely gene-disrupting variants in CSDE1 (encoding a highly constrained RNA binding protein) among patients with autism and related neurodevelopmental disabilities. Analysis of 17 patients identifies common phenotypes including autism, intellectual disability, language and motor delay, seizures, macrocephaly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 58 publications
(91 reference statements)
2
59
1
Order By: Relevance
“…Studies in humans and animal models have revealed aberrations in dendritic spine architecture in several psychiatric disorders including depression and others related to stress (Edfawy et al, 2019;Guo et al, 2019;Yang et al, 2020). Changes in spine density and organization are thought to contribute to the behavioral disorder caused by stress exposure (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans and animal models have revealed aberrations in dendritic spine architecture in several psychiatric disorders including depression and others related to stress (Edfawy et al, 2019;Guo et al, 2019;Yang et al, 2020). Changes in spine density and organization are thought to contribute to the behavioral disorder caused by stress exposure (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The human ortholog, Unr/CSDE1, is linked to several cellular processes, including cell migration, differentiation, and apoptosis, where it predominantly acts as a cytoplasmic RBP to regulate translation and stability of its target mRNAs ( Boussadia et al., 2003 ; Dormoy-Raclet et al., 2005 ). Attesting to its important roles in post-transcriptional regulation, Unr/CSDE1 has been linked to diseases, including Diamond-Blackfan anemia, autism, and cancer progression ( Fishbein et al., 2017 ; Guo et al., 2019 ; Horos and von Lindern, 2012 ; Sanders et al., 2012 ; Wurth et al., 2016 ; Xia et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, CSDE1 is a negative regulator of neural differentiation in human stem cells because loss of CSDE1 accelerates neurogenesis (Ju Lee et al, 2017). Second, likely gene-disrupting variants in CSDE1 are associated with autism spectrum disorder (Guo et al, 2019). Interestingly, it was reported that CSDE1 knockdown promotes neurite and axon outgrowth (Guo et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Second, likely gene-disrupting variants in CSDE1 are associated with autism spectrum disorder (Guo et al, 2019). Interestingly, it was reported that CSDE1 knockdown promotes neurite and axon outgrowth (Guo et al, 2019). These results stimulated us to hypothesize that CSDE1 is a key target of Gpr151 mRNA for its non-coding function through non-ribosomal RBPs.…”
Section: Resultsmentioning
confidence: 99%